2021
DOI: 10.3390/ijms23010469
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Expression Profile of OSCA Gene Family Members in Triticum aestivum L.

Abstract: Hyperosmolality and various other stimuli can trigger an increase in cytoplasmic-free calcium concentration ([Ca2+]cyt). Members of the Arabidopsis thaliana (L.) reduced hyperosmolality-gated calcium-permeable channels (OSCA) gene family are reported to be involved in sensing extracellular changes to trigger hyperosmolality-induced [Ca2+]cyt increases and controlling stomatal closure during immune signaling. Wheat (Triticum aestivum L.) is a very important food crop, but there are few studies of its OSCA gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 44 publications
5
23
0
Order By: Relevance
“…In plants, several calcium channels have been characterized to find that they not only function to mediate the response to abiotic and biotic stresses, but are also involved in growth regulation and biosynthesis [ 12 , 13 , 14 , 15 , 16 , 17 ]. Among them, the hyperosmolality-gated calcium-permeable channel family ( OSCA ) is one of the most important and well-studied calcium channels participating in osmotic adjustment [ 18 , 19 ]. In light of its significance, the OSCA family has been identified in many plant species, including 15 OSCA members found in A. thaliana , 11 in rice [ 18 ], 42 in wheat [ 19 ], 12 in maize [ 20 , 21 ], 13 in mung bean [ 22 ], as well as 35 in cotton [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In plants, several calcium channels have been characterized to find that they not only function to mediate the response to abiotic and biotic stresses, but are also involved in growth regulation and biosynthesis [ 12 , 13 , 14 , 15 , 16 , 17 ]. Among them, the hyperosmolality-gated calcium-permeable channel family ( OSCA ) is one of the most important and well-studied calcium channels participating in osmotic adjustment [ 18 , 19 ]. In light of its significance, the OSCA family has been identified in many plant species, including 15 OSCA members found in A. thaliana , 11 in rice [ 18 ], 42 in wheat [ 19 ], 12 in maize [ 20 , 21 ], 13 in mung bean [ 22 ], as well as 35 in cotton [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the hyperosmolality-gated calcium-permeable channel family ( OSCA ) is one of the most important and well-studied calcium channels participating in osmotic adjustment [ 18 , 19 ]. In light of its significance, the OSCA family has been identified in many plant species, including 15 OSCA members found in A. thaliana , 11 in rice [ 18 ], 42 in wheat [ 19 ], 12 in maize [ 20 , 21 ], 13 in mung bean [ 22 ], as well as 35 in cotton [ 23 ]. The expression profile of OSCA genes were also systematically investigated under diverse abiotic stresses in different plant species, which demonstrated their differential roles in stress response and tolerance [ 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…OSCA proteins are distributed as multigene families in eukaryotic species possessing conserved DUF221 (Domain of Unknown Function 221) with 11 transmembrane helices and a cytosolic soluble domain that forms a homodimer of two pores [ 12 , 13 , 14 ]. Genome-wide survey and identification of the OSCA gene family have been widely conducted in different species, and the gene number ranged from 11 members in rice to 42 members in wheat [ 10 , 15 , 16 , 17 ]. In recent years, many reports have indicated the roles of OSCA genes in osmotic-related abiotic stress response.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, it often suffers from various biotic stresses (such as powdery mildew and downy mildew) and abiotic stress (drought, cold, osmotic, and salt) under natural conditions, which seriously affect its yield and quality [ 22 , 23 ]. The OSCA family has been investigated in many plant species, such as Arabidopsis [ 10 ], rice [ 15 ], maize [ 18 , 24 ], and wheat [ 17 ], whereas the members of OSCA family in cucumber have not been identified. In this study, we systematically identified the OSCA gene family members and analyzed their sequence characteristics, promoter regions, and tissue expression patterns.…”
Section: Introductionmentioning
confidence: 99%